Improving food safety in Asia through increased capacity in ecohealth - Hall, D.C.; Hung Nguyen-Viet; Willyanto, I.; Tung, D.X.; Chotinun, S. (Academic Journals, 2013)
Interest has increased considerably in the last five years in transdisciplinary approaches to addressing the precipitating factors of emerging infectious and zoonotic diseases. During this time, several One Health and ecohealth initiatives have begun in Asia. This paper reports on recommendations coming out of one such initiative (the Building Ecohealth Capacity in Asia project) and outlines a strategy for promoting an ecohealth approach in research and in practice relevant to prioritized concerns relating to reducing zoonotic disease in Asia. The three main aspects of the strategy that are presented and discussed include: (1) Promote transdisciplinary approaches to understanding the complexity of zoonotic disease that compromise food safety; (2) increase teaching and application of ecohealth in medical sciences and other subjects relevant to food safety; and (3) bring ecohealth and One Health approaches into health policy discussions, particularly where these discussions influence policy formulation. Main constraints to applying such a strategy include limited awareness and knowledge of ecohealth and One Health, lack of willingness to engage in a transdisciplinary setting, restricted capacity to change academic curricula, rigid institutional frameworks for problem solving, and availability of funding. Suggestions for reducing these constraints are addressed.816600